Kajian Arsitektur pada Masjid Bingkudu di Minangkabau Dilihat dari Aspek Nilai dan Makna - Fatimah, Dina (Program Studi Desain Interior Unikom, 2015)
Minangkabau philosophy of life is represented in â€œalam takambang jadi guruâ€ that is fundamentally based upon tradition, religion, and the Al-Quran (adat basandi syaraâ€™, syaraâ€™basandi kitabullah). This philosophy is also implemented in its societyâ€™s works of art, particularly in architecture. The Minangkabau architecture under discussion in this research is an ancient mosque called Bingkudu in Candung, Agam Regency. This research is a study of architecture on Bingkudu Mosque in Minangkabau as seen from point of view of value and meaning. The research describes Bingkuduâ€™s visual elements, then searches and collects the data regarding their value and meaning. The research shows that the value and meaning design of architectural design of Bingkudu Mosque do not stray from the value of monotheism. Tradition and religion go hand in hand without any significant differences in this principle and shape on the visual elements. This mosque also undergo an acculturation between the old concept adhering to indigenous culture (have already undergone acculturation) with the concept of Islamic architectural designs. This proves that the Minangkabau society is open to other cultures. Key words:culture, Minangkabau, mosque, religion, tradition, value and meaning.